The bad batch [videorecording (DVD)] - Amirpour, Ana Lily; Amirpour, Ana Lily; Waterhouse, Suki, 1992-; Momoa, Jason; Reeves, Keanu (Virgil Films, 2017)
In a dystopian Texas wasteland, a man and woman find love in a community of cannibals.